Modeling of reinforced concrete sub-frame under cyclic load reversals - Khoo, Jyh Hao (2012)
A study of the strength and deformation characteristics of reinforced concrete structure under cyclic load reversals by means of a computational model is presented in this article. A beam-column sub-frame tested under reversed cyclic loading at NTU, Singapore was modeled and analyzed using strut-and-tie method to capture its cyclic hysteretic responses and to explore the possible force flows from beam and column to the joint core. The model was developed based on crack patterns observed on the tested concrete specimen, and was analyzed using DRAIN-2DX. The modeling procedure for different truss elements of the model is described herein. The analytical study reveals that the strut-and-tie method is capable of modeling to a satisfactory accuracy the cyclic hysteretic response of a reinforced concrete structure observed in the full-scale test.